A virtual reality paradigm to assess episodic memory: Validation-dataset for six parallel versions and a structured behavioral assessment - Yvonne Höller; Christopher Höhn; Fabian Schwimmbeck; Gaën Plancher; Eugen Trinka (Data in Brief, 2020)
In the epilepsy monitoring unit of the Department of Neurology at the University Clinic of Salzburg 20 adult patients were recruited to participate in a validation of 6 parallel versions of the virtual reality test for episodic memory. Patients were tested up to 7 times, i.e. twice a day, in the morning and evening, beginning on Monday evening. Each session consisted of learning a new town and immediate recall for this town. All sessions but the first one included also delayed recall of the previously learned town and a recognition test. Recall included the sub-scales what, details, when, egocentric where and allocentric where. Recognition memory was tested by presenting the patients 30 sentences of which 15 were true and 15 were false.While not all patients completed the full testing schedule, at immediate recall for 9 patients a full data set (7 sessions) is available. All patients were free of antiepileptic medication (N = 19) or medication was kept constant across the week (N = 1).This data can be used to demonstrate the feasibility to use the virtual reality test in the epilepsy monitoring unit e.g. to monitor effects of seizures or medication on episodic memory. Keywords: Virtual reality, Epilepsy monitoring unit, Episodic memory, Delayed recall